The impact of use of traditional medicine on pregnancy outcomes in Chipinge District; Manicaland Province: Zimbabwe - Tinashe, Kureya; Miriam, Chitura; Auxillia, Professor Chideme Munodawafa (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The prevalence of use of traditional medicine to prepare for child birth in Chipinge district ispronounced. No research has been done to examine the impact of use of traditional medicineon pregnancy outcomes in Chipinge district. It is from this background that this study wasconducted to determine the impact of traditional medicine on pregnancy outcomes. Anunmatched 1:1 case control study design was used to assess the pregnancy outcomes of 40mothers who used traditional medicine and 40 mothers who did not. The mothers were between20 and 35years of age, parity range of 1 to 4, identified from the delivery record of Mahenyeand Mabee record book, period July 2015 and February 2016. The most commonly usedtraditional medicine was elephant dung. A young age (20-25years) and perceiving thattraditional medicine is effective were associated with using traditional medicine. Lowknowledge of traditional medicine and low knowledge of health risks of traditional medicinewas protective of using the medicine. Precipitate labour was significantly associated with theuse of traditional medicine for childbirth.